To the question about protection of honor, dignity and business reputation of an individual - Великанова, Марина Миколаївна; Хрик, Аліна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Article is devoted to the conceptual foundations of the functioning mechanism of protection of honor, dignity and business reputation, and the shortcomings of legal regulation of these rights.